Relationships between Viral Load, Neuroimaging and Neuropsychological Performance in Persons Living with HIV - Cooley, Sarah A. (J Acquir Immune Defic Syndr, 2021)
BACKGROUND: This study examined whether recommended viral load (VL) classifications by the Department of Health and Human Services map onto changes in brain integrity observed in people living with HIV (PLWH). METHODS: 349 PLWH on combination antiretroviral therapy (cART) meeting criteria for virologic suppression (VS) (VL ≤ 20 copies/mL; n=206), “low-level viremia” (LL; 20–200 copies/mL; n=63) or virologic failure (VF) (> 200 copies/mL; n=80), and 195 demographically similar HIV- controls were compared on cognition and brain volumes from 10 regions of interest that are sensitive to HIV. Changes in cognition and brain volumes were examined in a subset of PLWH (n=132) who completed a follow-up evaluation (mean interval=28 months) and had no change in treatment regimen. RESULTS: Significant differences in cognition and brain volumes were observed between the HIV- control and VS compared to the VF groups, with few differences observed between the three PLWH subgroups. Longitudinally, PLWH who continued to have VF exhibited a greater decline in cognition and brain volumes compared to PLWH who remained VS. Observed longitudinal changes in cognition correlated with brain volume changes. CONCLUSION: PLWH with continued VF (consecutive VL measurements of >200 copies/mL) represent a cause for clinical concern, and may benefit from change in treatment in addition to consideration of other potential etiologies of VF to reduce loss of brain integrity.